Pengaruh Viral Marketing dan Online Customer Review terhadap Minat Beli Konsumen Marketplace Shopee dikalangan Mahasiswa S1 Fakultas Ekonomi dan Bisnis Universitas Jambi - Sausan Salsabilla Septia Nanda; Husni Hasbullah; Sylvia Kartika Wulan B (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This research is the result of quantitative research which aims to answer questions about the influence of Viral Marketing and online Customer Reviews on the buying interest of Shopee marketing consumers. The research method used is quantitative research and the sampling technique uses a purposive sampling method with a sample size of 98 respondents. The data collection technique uses a questionnaire with the help of a Google form which is processed using SPSS version 27 and the data analysis technique uses multiple linear regression. This research focuses on undergraduate students from the Faculty of Economics and Business, Jambi University as young, dynamic and technology-savvy consumers, who very often use the Shopee e-commerce application to purchase various products. So Shopee has become one of the largest e-commerce which is very popular in Indonesia. The results of this research show that Shopee Viral Marketing has a positive effect on buying interest. Then online Shopee Customer Reviews have a positive effect on buying interest. Furthermore, based on the results of simultaneous test statistical calculations, it shows that Shopee's Viral Marketing and Online Customer Reviews have a simultaneous influence on Shopee marketplace consumer buying interest among undergraduate students at the Faculty of Economics and Business, Jambi University. For the Shopee marketplace, it is recommended to increase Viral Marketing promotions and maintain online Customer Reviews on the Shopee marketplace which is already popular among the public. Apart from that, Shopee also needs to create the latest innovations in order to accommodate customer desires and expectations, in order to maintain competitiveness and product relevance in the market.